2006
DOI: 10.1128/jb.01974-05
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Competence Gene Homologs Are Essential for Competitive Fitness and the Use of DNA as a Nutrient

Abstract: Natural genetic competence is the ability of cells to take up extracellular DNA and is an important mechanism for horizontal gene transfer. Another potential benefit of natural competence is that exogenous DNA can serve as a nutrient source for starving bacteria because the ability to "eat" DNA is necessary for competitive survival in environments containing limited nutrients. We show here that eight Escherichia coli genes, identified as homologs of com genes in Haemophilus influenzae and Neisseria gonorrhoeae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
138
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(147 citation statements)
references
References 66 publications
(63 reference statements)
5
138
0
2
Order By: Relevance
“…Extracellular DNA has been detected in virtually all environments inhabited by bacteria, 16,18,19,[50][51][52] and has also been implicated as a major structural component of bacterial biofilms. 24,25,53 Thus, it is possible that bacterial DNA recognition by a surface receptor has evolved as a signal to alert the immune system to the presence of bacterial invasion, mainly in infections which course with bacteria growing as biofilms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Extracellular DNA has been detected in virtually all environments inhabited by bacteria, 16,18,19,[50][51][52] and has also been implicated as a major structural component of bacterial biofilms. 24,25,53 Thus, it is possible that bacterial DNA recognition by a surface receptor has evolved as a signal to alert the immune system to the presence of bacterial invasion, mainly in infections which course with bacteria growing as biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous studies have shown that Escherichia coli strains that consume DNA are more fit than those mutants unable to metabolize DNA. 19 On the other hand, several independent observations have adjudicated an important role for DNA in the formation and composition of biofilms, which are structured communities of cells enclosed in self-produced hydrated polymeric matrix adherent to an inert or living surface. 24,25 Thus, we hypothesized that extracellular DNA in bacterial microenvironments might be recognized by a neutrophil surface molecule able to trigger neutrophil activation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown in several species that bacteria can indeed use DNA as a nutrient (Jorgensen et al 1994;Finkel and Kolter 2001;Palchevskiy and Finkel 2006;Pinchuk et al 2008). For example, Escherichia coli can grow on DNA as the sole source of carbon and energy (Finkel and Kolter 2001), and eight genes have been identified that are necessary for DNA uptake and that provide a competitive advantage during stationary phase (Palchevskiy and Finkel 2006). Pinchuk et al (2008) reported that Shawanella spp.…”
Section: Our Model In the Light Of Empirical Datamentioning
confidence: 99%